Optimalisasi Deteksi Dini Penyakit Kardiovaskular Melalui Skrining Trigliserida Pada Usia Produktif - Frisca; Alexander Halim Santoso; Farell Christian Gunaidi; Nikita Tan; Steve Geraldo Bustam (CV. Akira Java Bulu, 2025)
Elevated triglyceride levels are a significant risk factor for cardiovascular disease, which remains one of the leading causes of death in Indonesia and globally. Screening for triglyceride levels among the productive-age population is essential for early detection and prevention of cardiovascular complications. This community service activity involved 49 adult participants in Danau Sunter, North Jakarta, where triglyceride level screening was conducted through blood tests by professional health workers. The screening results revealed that 46.94% of participants had elevated triglyceride levels, indicating a substantial risk for metabolic disorders and cardiovascular disease. Participants with high triglyceride levels received education on lifestyle modifications and appropriate preventive measures. This activity effectively identified individuals at risk for hypertriglyceridemia and increased community awareness of the importance of maintaining cardiovascular health through routine screening and lifestyle changes. Keywords: Triglycerides, Cardiovascular Disease, Screening, Productive Age